Exploitation of CD3ζ to enhance TCR expression levels and antigen-specific T cell function - Degirmencay, Abdullah; Thomas, Sharyn; Holler, Angelika; Burgess, Samuel; Morris, Emma C.; Stauss, Hans J. (Frontiers in Immunology, 2024)
The expression levels of TCRs on the surface of human T cells define the avidity of TCR-HLA/peptide interactions. In this study, we have explored which components of the TCR-CD3 complex are involved in determining the surface expression levels of TCRs in primary human T cells. The results show that there is a surplus of endogenous TCR a/b chains that can be mobilised by providing T cells with additional CD3g,d,e,z chains, which leads to a 5-fold increase in TCR a/b surface expression.The analysis of individual CD3 chains revealed that provision of additional z chain alone was sufficient to achieve a 3-fold increase in endogenous TCR expression.Similarly, CD3z also limits the expression levels of exogenous TCRs transduced into primary human T cells. Interestingly, transduction with TCR plus CD3z not only increased surface expression of the introduced TCR, but it also reduced mispairing with endogenous TCR chains, resulting in improved antigen-specific function. TCR reconstitution experiments in HEK293 cells that do not express endogenous TCR or CD3 showed that TCRa/b and all four CD3 chains were required for optimal surface expression, while in the absence of CD3z the TCR expression was reduced by 50%.Together, the data show that CD3z is a key regulator of TCR expression levels in human T cells, and that gene transfer of exogenous TCR plus CD3z improved TCR surface expression, reduced TCR mispairing and increased antigen-specific function.